2020
DOI: 10.1177/1071100720968831
|View full text |Cite
|
Sign up to set email alerts
|

First Metatarsophalangeal Arthrodesis After Failed Distal Chevron Osteotomy for Hallux Valgus

Abstract: Background: The purpose of this study was to compare the clinical outcomes after first metatarsophalangeal (MTP) joint arthrodesis for hallux rigidus between patients who underwent primary arthrodesis and those who had had a prior surgery for hallux valgus. Methods: Our design was a retrospective cohort study comparing 29 patients who underwent primary arthrodesis (primary group) and 34 patients with hallux rigidus after hallux valgus surgery (secondary group). The clinical assessment included the American Ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…First MTP fusion reliably produces satisfactory patient outcomes including improved function and decreased pain, 2,4,5,36 and remains the gold standard in the treatment of advanced first MTP arthritis. 37 A 2021 systematic review of 570 patients undergoing first MTP arthrodesis conducted by França et al 38 showed greater than 90% patient satisfaction rate with revision rates ranging from 0% to 20.5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First MTP fusion reliably produces satisfactory patient outcomes including improved function and decreased pain, 2,4,5,36 and remains the gold standard in the treatment of advanced first MTP arthritis. 37 A 2021 systematic review of 570 patients undergoing first MTP arthrodesis conducted by França et al 38 showed greater than 90% patient satisfaction rate with revision rates ranging from 0% to 20.5%.…”
Section: Discussionmentioning
confidence: 99%
“…First metatarsophalangeal joint (MTPJ) arthrodesis is a commonly performed procedure for patients with various disorders of the first ray including hallux rigidus, severe hallux valgus, failed 1st MTPJ replacement, and failed hallux valgus correction. 1 Outcomes are generally favorable with reported fusion rates greater than 90% with commensurate improvements in patient-reported outcomes including function, satisfaction, and pain [2][3][4][5] Patients can return to being active and participate in sports such as golf and tennis with no functional consequence. 6 The importance of various surgical factors on patient outcomes of first MTP joint arthrodesis has been previously studied, 1 and while certain patient-related factors have generally been associated with worse outcomes in elective foot and ankle surgery, 3,[7][8][9][10][11] there is limited data on how these specifically correspond to Effect of Obesity on Patient-Perceived Outcomes After First Metatarsophalangeal Joint Arthrodesis patients undergoing 1st MTPJ arthrodesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indications include end-stage MTP osteoarthritis, selected cases of hallux valgus, inflammatory arthritis, and failed first MTP joint surgery. 8 , 10 , 23 , 47 , 50 The procedure is commonly performed in patients with advanced hallux rigidus. 22 In such cases, arthrodesis is supposed to provide more effective pain relief when compared to several motion-preserving alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of joint motion compensation affects dynamic parameters such as joint load [ 10 ]. There are FMJ lesions in many patients with hip, knee, and ankle lesions, especially those with knee arthritis [ 11 ]. At present, there is a lack of literature on this relationship, according to the preliminary experimental basis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%